(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, history and improvement the style of thought were analyzed. Additionally, the author scrutinized comparatively the style of thought and the approach of scholars of different times. The author asserts that the meaning of the style of thought is concerned genetically with the scientific work of the scholars.